Skin Moisture Profile of Normal Skin and Inflammatory Skin Disease Using Skin Analyzer - Alida Widiawaty; Sukasihati; Kharina Puteri Ayda; Salsabila Azura Nasution (Future Science, 2022)
The skin has several functions which related to each other. It consists of 3 layers with EHT epidermis on the top layer. It serves to provide a barrier of protection against skin external threats and has one of the important functions of the skin. The structure of the stratum corneum is the main factor that regulates the transportation of fluid in the skin to retain skin moisture. One of the characteristics of healthy skin is moisture. Dry skin is prone to dermatoses, such as dermatitis. Since skin moisture is important, we need to measure the level of water in the epidermis. The faster the diagnosis, the faster the treatment. This study uses a cross-sectional design, conducted at one of the general hospitals in Pekanbaru. Skin moisture examination was carried out by determining the percentage of water content in the epidermis using a portable skin analyzer on the skin surface of healthy people, and normal (non-lesional skin lesions) of subjects diagnosed with dermatitis. The mean of subjects without dermatoses is 36,4, the non-lesional skin of subjects with dermatoses is 36.4, and the skin lesion of the subject was 12,6. Data were analyzed by t-test. There is a significant difference between non-lesional and lesional skin with a p-value <0,05.